ANALISIS TATA KELOLA KEUANGAN ASURANSI JASA DALAM MENILAI KINERJA OPERASIONAL USAHA SECARA PERIODIK - Ibrahim Hafid (Jurnal Keuangan dan Perbankan, 2016)
AbstractThe aimed of this Research is into racite and evaluate performance operational Business Corporate Insurance Service According Time Periode with Benefit and will given input for upgrade and growth Business Insurance in Indonesia. This Research Performance Corporate at Measured with Early Warning Systems (EWS) Financial Ratio, Relevant and Continued Analysis for Income Corporate and to Know Inclanation up and down from each accounts in Balanced and Income Statement.The Result of this Research with based EWS in Liquidity,Solvency and Technical Ratio PT. Asuransi Jasa XYZ, Tbk in the Time Research Experiance up and down but with out one periode to exceed minimum Limit Liquidity Deciding by Goverment is amount 120% (1,2) Net Premium at PT. Asuransi Jasa XYZ, Tbk to Set-Up Every year in the time periode Research, but net premium achived corporate from 2010 until 2013 years is under Net Premium by Decided Government.